2016
DOI: 10.3346/jkms.2016.31.7.1114
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Korean-Version of the Clinical Assessment Interview for Negative Symptoms of Schizophrenia (CAINS)

Abstract: The Clinical Assessment Interview for Negative Symptoms (CAINS) was developed to overcome the limitations of existing instruments and reflect the current view of negative symptoms. The aim of the present study was to evaluate the reliability and validity of the Korean version of the Clinical Assessment Interview for Negative Symptoms (K-CAINS). Inpatients (n = 49) and outpatients (n = 70) with schizophrenia were recruited from three institutions. The confirmative factor analysis, test-retest reliability, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
4
13
1
Order By: Relevance
“…The three-factor structure was found to be different from the original CAINS validation (Kring et al, 2013), as well as from validations done in other languages (Engel et al, 2014;Chan et al, 2015;Valiente-Gómez et al, 2015;Jung et al, 2016), which mostly found a two-factor structure ("Motivation and Pleasure" and "Expression"). A recent cross-cultural confirmatory factor analysis found that a hierarchical model, in which motivational and expressive second-order factors are included with the five first-order factors (alogia, anhedonia, avolition, asociality, and blunted affect), has equally good fit as a model which includes only the first-order factors (Ahmed et al, 2019).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The three-factor structure was found to be different from the original CAINS validation (Kring et al, 2013), as well as from validations done in other languages (Engel et al, 2014;Chan et al, 2015;Valiente-Gómez et al, 2015;Jung et al, 2016), which mostly found a two-factor structure ("Motivation and Pleasure" and "Expression"). A recent cross-cultural confirmatory factor analysis found that a hierarchical model, in which motivational and expressive second-order factors are included with the five first-order factors (alogia, anhedonia, avolition, asociality, and blunted affect), has equally good fit as a model which includes only the first-order factors (Ahmed et al, 2019).…”
Section: Discussioncontrasting
confidence: 81%
“…Expressive determinants are comprised of reduced verbal and non-verbal communicative output. The CAINS instrument has since been translated and validated in several countries (Engel et al, 2014;Chan et al, 2015;Valiente-Gómez et al, 2015;Jung et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the validity was verified using the confirmatory factor analysis (CFA), and the convergent validity was measured. Convergent validity can be considered appropriate when the standardized coefficient (SC) is 0.5 or more, the average variance extracted (AVE) value is 0.5 or more, and the value of the construct reliability (CR) is 0.7 or more ( 15 16 17 ). The result of the validity analysis showed that the SC was 0.5 or more, the AVE was 0.5 or more, and the CR 0.7 or more for the independent variables, the mediator variables, and the dependent variable.…”
Section: Resultsmentioning
confidence: 99%
“…However, few CFAs have been conducted on negative symptom scales, and those that have been published do not strongly support the 2-dimensional structure. For example, 2 studies attempted to validate the 2-factor structure using Korean 19 and Chinese 20 translations of the CAINS. Both concluded that the CAINS was best fit by a 2-factor structure, with dimensions reflecting MAP and EXP.…”
Section: Introductionmentioning
confidence: 99%